Spectrum of radiological presentations of Intracranial Glioma among the Indian population - Muchhoria, Shilpi; Dixit, Sourabh; Banga, Manpreet Singh; Ghosh, Partha; Nadkarni, Abhishek; Pahwa, Nakul (Asian Journal of Medical Sciences, 2020)
Background: Gliomas comprises the group of most common primary tumour of central nervous system. The current study was undertaken to evaluate the various usual and unusual radiological presentations among the patients of glioma among the Indian population. Aims and Objective: The aim of the current study was to observe the various radiological presentations of glioma occurring among the subjects. It was also intended to correlate the radiological and histopathological grading in glioma among subjects. Materials and Methods: The current study was a prospective observational study carried out among seventy-five patients admitted in a tertiary care hospital in Eastern India with provisional diagnosis of supratentorial glioma and operative biopsy confirmed to be Glioma. Result: The most common grade of tumour encountered was grade IV tumour. Of the clinical features, 70.66 % patients had hypodense lesion, 25.33% patients had iso dense and hypodense (mixed density) lesion and 3 patients had hyperdense lesion on CT Brain. On MRI in T1 Weighted images, 81.33% patients had hypointense lesion lesion on MRI T1 image. On T2 Weighted Images, 76% patients had hyperintense lesion., 77.33% demonstrated heterogenous enhancement. Ring enhancement was seen in 9 cases Minimal to no enhancement was seen in 8 cases. MRS showed maximum cases had Choline peak with altered Choline: creatinine ratio and decreased NAA peaks. Conclusion: Good imaging interpretations is crucial for planning of surgical excision and adjuvant radiotherapy. This review has been put to solve the basic problem in interpreting the Ct Scan and MRI of Glioma.